Weightbearing in Select Geriatric Ankle Fractures Following Open Reduction Internal Fixation: Short Scientific Report - Atticus Coscia MD; Michal Jandzinski MD; Paul Talusan MD; Jaimo Ahn MD PhD (Foot & Ankle Orthopaedics)
Background: Geriatric ankle fractures are increasingly common. Previous work has suggested that early weightbearing following ankle fracture fixation is safe in nongeriatric patients. However, limited data is available regarding the safety of immediate weightbearing following fixation of geriatric ankle fractures using standard open reduction internal fixation techniques. Methods: Forty-four patients aged 65 years or older treated for rotational ankle fractures were propensity matched, with 22 patients following a nonweightbearing (NWB) protocol and 22 were allowed to weightbear immediately (WBAT) in a controlled ankle motion boot at all times. Primary outcomes included hardware failure and postoperative complications. Group differences in continuous variables were analyzed via Student t test whereas Fisher exact tests were used to analyze the differences in categorical variables. Complication-free survival and hardware failure–free survival were compared using the log-rank (Mantel-Cox) test. Results: There were no hardware failures in the WBAT group and 1 hardware failure in the NWB group; the difference was not statistically significant. There was no difference in incidence of postoperative complications, rate of hardware failure, or PROM scores. Conclusion: In this preliminary study group, we found that immediate weightbearing following fixation of geriatric ankle fractures was not associated with increased hardware failure or postoperative complications. Level of Evidence: Level IV, retrospective cohort.